2018
DOI: 10.1021/acs.jafc.8b05345
|View full text |Cite
|
Sign up to set email alerts
|

Revealing of MicroRNA Involved Regulatory Gene Networks on Terpenoid Biosynthesis in Camellia sinensis in Different Growing Time Points

Abstract: Tea, made from leaves of Camellia sinensis, has long been consumed worldwide for its unique taste and aroma. Terpenoids play important roles not only in tea beverage aroma formation, but also in the productivity and quality of tea plantation due to their significant contribution to light harvesting pigments and phytohormones. To date, however, the regulation of terpenoid synthase genes remains unclear. Herein, the analyses of metabolomics, sRNAs, degradome, and transcriptomics were performed and integrated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 58 publications
1
43
0
Order By: Relevance
“…The TPS gene is indispensable for the production of the most abundant and structurally diverse terpenoids influencing tea aroma. Moreover, high TPS expression level facilitates the conversion of precursors to various terpenoids (Chen et al, 2011b;Zhao et al, 2018). In the present study, high LTCONS_00043160 expression level inhibited TPS expression in the IW.…”
Section: Discussion the Expression Levels Of The Identified Differentsupporting
confidence: 43%
“…The TPS gene is indispensable for the production of the most abundant and structurally diverse terpenoids influencing tea aroma. Moreover, high TPS expression level facilitates the conversion of precursors to various terpenoids (Chen et al, 2011b;Zhao et al, 2018). In the present study, high LTCONS_00043160 expression level inhibited TPS expression in the IW.…”
Section: Discussion the Expression Levels Of The Identified Differentsupporting
confidence: 43%
“…Many known additional regulations in other plants could be also involved in the BR priming, including small RNA regulation [ 43 , 63 , 64 , 65 , 66 ], lncRNA regulation [ 67 ], alternative splicing in transcripts [ 65 , 68 ], and methylation regulation [ 69 ]. These additional regulations may work in a network manner under drought stress after BR-priming and are worth of dissecting in future using omics methods [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that 80–90% of land plants are colonized by AM fungi which can provide mineral nutrients to the plant and enhance plant resistance to adverse environments [10]. Although a large number of non-coding RNAs have been identified in animal and plant species [49,50,51,52], the profile of lncRNAs in plant root symbiosis with AM fungi has not been explored. In the present study, as many as 5941 lncRNAs were identified from the maize roots colonized with AM fungus.…”
Section: Discussionmentioning
confidence: 99%